CT atlas of adult congenital heart disease - Mazur, Wojciech; Siegel, Marilyn J.; Miszalski-Jamka, Tomasz; Pelberg, Robert (Springer London Imprint: Springer, 2013)
Improvements in surgical and medical management of congenital heart disease (CHD) result in an increased life expectancy and a greater number of children living into adulthood. Consequently, adult cardiologists are caring for increasing numbers of patients with congenital heart defects.  In many instances, these patients have undergone palliative but not corrective procedures and may be at higher risk of cardiovascular morbidity and mortality. In the past several years, the use of CT angiography (CTA) has increased, driven mainly by technical improvements that allow shorter imaging times and high spatial and temporal resolution. Thus, CTA combines widespread availability with the advantages of volumetric data acquisition, short acquisition times, and the possibility of simultaneous evaluation of myocardial and extracardiac structures, ventricular function and coronary anatomy making it a very appealing imaging modality in CHD patients. CT Atlas of Adult Congenital Heart Disease is an all inclusive, invaluable tool to describe the features of classic CHD, hereditary cardiomyopathies and aortopathies. It includes comprehensive pathology descriptions and discussions of the utility of CTA in the diagnosis of all forms of adult CHD.  The many CTA images and illustrations demonstrate the pathologies and provide a framework for recognizing patterns of CHD in adult patients.  It also includes pre-procedural pediatric CHD cases to allow better understanding of CHD anatomy and pathophysiology, and thus will be essential reading for all pediatric and adult cardiologists and radiologists involved in the management of these patients.